Peran Public Relations Dalam Implementasi Program CSR PT Semen Indonesia (Persero) Tbk - Cahayani, Fitrania Yunsafa; Amalia, Diana (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
PT Semen Indonesia (Persero) Tbk SIG as the largest cement producing company in Indonesia which is shaded by BUMN. This study aims to determine the public relations strategy of PT Semen Indonesia (Persero) Tbk, through its corporate social responsibility (CSR) program in maintaining the company's image. In maintaining the company's image, public relations communicates CSR programs that have been implemented through internal and external media. This study uses the concept of public relations, public relations strategy, image, CSR and communication as the approach used in knowing the GIS public relations strategy in maintaining the company's image. This research use desciptive qualitative approach. The results of this study indicate that in analyzing the strategy in maintaining the company's image through CSR programs, which go through four stages of the public relations process, namely: finding the facts and defining the problem, planning and programming, action and communication, and evaluation. In this strategy stage, packaging communication through media is attractive and easy for the public to access so that it can maintain a positive image in the eyes of the public and stakeholders. Keywords: Public Relations, CSR, Communication, Image..